The liberators - Lynch, Chris, 1962- (Lynch, Chris, 1962- World War II, 2015)
When Nick Nardini enlists in the Marine Corps' new paratrooper combat unit at the start of World War II, he has to talk his best friend, Zachary Klecko, into joining him in what he sees as an adventure--but from boot camp on it is clear that Zach is much more serious about the war than Nick is, at least until they are assigned to one of the POW recovery teams on the Japanese mainland.